2003
DOI: 10.1002/ijc.11222
|View full text |Cite
|
Sign up to set email alerts
|

Persistence and load of high‐risk HPV are predictors for development of high‐grade cervical lesions: A longitudinal French cohort study

Abstract: Oncogenic HPV types are the major cause of worldwide cervical cancer, but only a small proportion of infected women will develop high-grade cervical intraepithelial neoplasia or cancer (CIN2/3؉). We performed a prospective study including 781 women with normal, atypical squamous cells of undetermined significance (ASCUS) or low-grade squamous intraepithelial lesion (LGSIL) cytology, and infected or not by high-risk (HR) HPV tested by Hybrid Capture II. Women were followed up every 6 months for a median period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

33
317
3
35

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 372 publications
(395 citation statements)
references
References 51 publications
33
317
3
35
Order By: Relevance
“…26 Most CIN 1 regress and infection with oncogenic HPV is thought to be clinically significant only if it is persistent. 27 Epidemiological studies have shown that about 10% of women with high-risk HPV infection develop high-grade CIN. 5,6,16 It is speculated that persistent infection by specific viral types, particularly HPV 16 and 18 has the greatest tendency to cause CIN 2/3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Most CIN 1 regress and infection with oncogenic HPV is thought to be clinically significant only if it is persistent. 27 Epidemiological studies have shown that about 10% of women with high-risk HPV infection develop high-grade CIN. 5,6,16 It is speculated that persistent infection by specific viral types, particularly HPV 16 and 18 has the greatest tendency to cause CIN 2/3.…”
Section: Discussionmentioning
confidence: 99%
“…5,6,16 It is speculated that persistent infection by specific viral types, particularly HPV 16 and 18 has the greatest tendency to cause CIN 2/3. 3, 27 Kjaer et al 25 demonstrated that the risk for low-grade and high-grade CIN was markedly increased if there were repeat positive tests for HPV, but the most substantial increase in risk was for high-grade CIN if the repeat positive test was for the same HPV type. The odds ratio for developing high-grade CIN in women having repeat positive tests was 192.7 for nonidentical and 813.0 for identical HPV types compared to women tested as negative on two occasions.…”
Section: Discussionmentioning
confidence: 99%
“…Viral load has been suggested as a marker of nontransient infection, and high HPV load in smears with normal cytology has been associated with the risk of developing dysplasia and carcinoma in situ (CIS) van Duin et al, 2002;Dalstein et al, 2003;Moberg et al, 2004). However, it is not known whether high viral load is also predictive of invasive cervical cancer, as past studies have pooled the outcomes of invasive cancers together with earlier stages of the disease (Lorincz et al, 2002;Sherman et al, 2002Sherman et al, , 2003Sun et al, 2002;Dalstein et al, 2003;Gravitt et al, 2003). Integration of high-risk HPV into the cell genome has been suggested to play a pivotal role in malignant transformation (Boshart et al, 1984;Cullen et al, 1991;Daniel et al, 1997).…”
mentioning
confidence: 99%
“…Assim, hoje se sabe que o tipo 16 é o mais prevalente em todo o mundo 1 , independentemente da gravidade da lesão escamosa, e, de maneira geral, os HPV identificados como de alto risco estão presentes em mulheres imunocompetentes em cerca de 20% dos quadros histológicos negativos, em 70% dosUNIOR UNIOR*, P *, P *, P *, P *, PAULO AULO AULO AULO AULO C C C C CÉSAR ÉSAR ÉSAR ÉSAR ÉSAR G G G G GIRALDO IRALDO Vários pesquisadores defendem a idéia de que a alta carga viral de HPV de alto risco teria uma importante relação com lesões intraepiteliais escamosas e sua maior gravidade 6,7,8,10,12,15,18,22 . Outros pesquisadores enfatizam a importância da persistência da alta carga viral por longo tempo, e não simplesmente uma medida isolada, assim como só teria valor a alta carga viral do HPV tipo 16, sem considerar os demais tipos 2,3,9,13,14,16,17 .…”
Section: Introductionunclassified
“…Assim, a persistência de vírus de alto risco 5 , alta carga viral 2, 6-15 , persistente alta carga viral 16,17,18 , expressão do marcador de proliferação MIB-1 19 e, finalmente, a expressão do marcador de supressão tumoral p16 INK4a 4,20,21 , estão sendo apontados como prováveis marcadores de diagnóstico de lesões escamosas de alto grau e de seu prognóstico. Vários pesquisadores defendem a idéia de que a alta carga viral de HPV de alto risco teria uma importante relação com lesões intraepiteliais escamosas e sua maior gravidade 6,7,8,10,12,15,18,22 . Outros pesquisadores enfatizam a importância da persistência da alta carga viral por longo tempo, e não simplesmente uma medida isolada, assim como só teria valor a alta carga viral do HPV tipo 16, sem considerar os demais tipos 2,3,9,13,14,16,17 .…”
unclassified